Предмет: Алгебра, автор: IIIyTHiK

1-√a     _   3-√a 
2√a-4       3√a-6

Ответы

Автор ответа: julyap
0
 frac{1- sqrt{a} }{2 sqrt{a} -4} - frac{3- sqrt{a} }{3sqrt{a} -6}= frac{1- sqrt{a} }{2( sqrt{a} -2)} - frac{3- sqrt{a} }{3(sqrt{a} -2)} = frac{1- sqrt{a} }{2( sqrt{a} -2)} - frac{3- sqrt{a}}{3(sqrt{a} -2)} = \ =  frac{3(1- sqrt{a}) }{6( sqrt{a} -2)} - frac{2(3- sqrt{a}) }{6(sqrt{a} -2)}  =  frac{3(1- sqrt{a} )-2(3- sqrt{a}) }{6( sqrt{a} -2)} = frac{3-3 sqrt{a}-6+2 sqrt{a}  }{6 sqrt{a}-12 } = \ = frac{-3- sqrt{a} }{6 sqrt{a}-12 } =- frac{ 3+sqrt{a} }{6 sqrt{a} -12}
Похожие вопросы